2018
DOI: 10.1021/acs.jpca.8b06535
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and Temperature Effects on Dynamics and Chiroptical Properties of Propeller Chirality and Toroidal Interaction of Hexaarylbenzenes

Abstract: Because of the unique interaction of radial aromatic blades, propeller-shaped hexaarylbenzenes (HABs) attract much research interest and find various practical applications. By introducing a small point-chiral group at the tip of aromatic blade(s), HAB becomes propeller-chiral to exhibit strong Cotton effects. Because of the dynamic nature of propeller chirality, the chiroptical properties of HAB critically responded to minute changes in the environment. Using a series of chiral HABs with one to six ( R)-1-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…The pressure dependence of H6 was also examined in hexane. In our previous investigation, we demonstrated that the shape of solvent molecule definitely matters in the observed (chir)optical responses of the HAB derivatives . As expected, the pressure dependence of H6 in hexane was somewhat different from those observed in methylcyclohexane.…”
Section: Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…The pressure dependence of H6 was also examined in hexane. In our previous investigation, we demonstrated that the shape of solvent molecule definitely matters in the observed (chir)optical responses of the HAB derivatives . As expected, the pressure dependence of H6 in hexane was somewhat different from those observed in methylcyclohexane.…”
Section: Resultsmentioning
confidence: 50%
“…This is in accord with our explanation where the contribution of the propeller against the toroidal conformation becomes dominant at higher pressure. Such significant spectral changes are characteristic for flexible HABs, owing to the synchronized unidirectional rotation of peripheral blades …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations